Shelf-life evaluation of virgin olive oil extracted from olives subjected to nonthermal pretreatments for yield increase. (April 2017) - Andreou, V.; Dimopoulos, G.; Alexandrakis, Z.; Katsaros, G.; Oikonomou, D.; Toepfl, S.; Heinz, V.; Taoukis, P.
Abstract: Critical process parameters for the yield and quality of olive oils are the temperature and treatment duration of the malaxation process. A balance between oil yield and quality must be achieved. Novel technologies such as High Pressure (HP) and Pulsed Electric Fields (PEF) that cause alterations to cell permeability, may promote the olive oil extraction process during malaxation, resulting in higher oil yields. Three different varieties of Olive fruits ( Tsounati, Amfissis and Manaki var.) were subjected to different HP (200 and 600 MPa, 25 °C for 1 and 5 min) and PEF (1.6–70.0 kJ/kg) process conditions before malaxation (30 min at 30 °C). The extraction yield was increased up to 18 and 16% for PEF and HP treated olive fruits, respectively. The shelf-life tests indicate that the oil quality from nonthermally pretreated olives is dependent on the technology and process conditions used. An increase of oil oxidative stability for PEF and HP treated olives was shown, compared to control samples. The results show that HP and PEF could be applied for the production of superior quality virgin olive oil with increased yield. Highlights: HP and PEF processing as pretreatments on whole olive fruits result in higher olive oil yields. HP and PEF pretreatments increase the oxidative stability of the oil. HP and PEF do not affect the quality indices of the oil.